The role of imunohistochemical analysis in the diagnosis of lung metastases - Blanuša, Ljuban; Lovrenski, Aleksandra; Baroš Brkljača, Marija (Archive of Oncology, 2023)
Background: Metastatic tumors are tumors whose primary origin is not the organ in which they are located, but have reached the target tissue by metastasis from the primary site of the tumor. The presence of metastases of the primary tumor in other organs is responsible for the highest number of cancer mortalities, and in addition, their presence significantly changes the treatment of an oncologic patient in relation to a patient to whom the primary tumor is not disseminated. The goal of this study was to determine the importance of immunohistochemistry in the diagnosis of metastatic lung tumors.Methods: A retrospective study included 84 patients with a pathohistologically proven metastatic lung disease at the Institute of Pulmonary Diseases of Vojvodina from April 1 2013 to March 31 2018. The material for pathohistological and immunohistochemical analysis was studied at the Institute for Histopathology and Molecular Diagnostics of the Institute.Results: Out of a total of 84 patients, in 42 (50%) patients, the origin of pulmonary metastases was colorectal cancer, 15 (17%) renal cell carcinoma, 11 (13%) breast cancer, 4 (4%) malignant melanoma, 3 (4%) leiomyosarcoma of the uterus, and in the other 9 (11%) individual tumor cases. Antibodies used in the immunohistochemical assay are CK20 and CDX2 (colorectal cancer), CD10, RCC, Vimentin (renal cell carcinoma), PR, ER, Mamaglobin (breast cancer), HMB45, S100, Vimentin, MelanA (melanoma) SMA, Myosin, Desmin (uterine leiomyosarcoma).Conclusion: For the purpose of faster and more precise diagnostic and timely treatment of patients with disseminated malignant disease, it is necessary to supplement the standard pathohistological analysis with immunohistochemistry analysis, which is an important method in determining the primary origin of metastatic tumors.Keywords: Lung Neoplasms; immunohistochemistry; pathology;  metastases.
Keywords: Lung Neoplasms; immunohistochemistry; pathology; metastases